(3efXheI aj EQK GdeQCIs - (3GdWHGWHGFj, GdMGFQj, eMeO HGbQ Hf GHj GdbGSe Hf MSf, J (B1331(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3Ef eGJ ef bO GTJQi CQVG LYd(B***(3ddHGFY GdNjGQ Ef QO GdHOds
(3BNQgG (B:s
(3hgd JQi GdeGfY gfG jbVj gfG HCf Jedc Kef GdCQVs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B154s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis